Integration of Biobanks in National eHealth Ecosystems Facilitating Long-Term Longitudinal Clinical-Omics Studies and Citizens' Engagement in Research Through eHealthBioR - Antoniades, Athos; Papaioannou, Maria; Malatras, Apostolos; Papagregoriou, Gregory; Müller, Heimo; Holub, Petr; Deltas, Constantinos; Schizas, Christos N. (Frontiers in Digital Health, 2021)
Biobanks have long existed to support research activities with BBMRI-ERIC formed as a European research infrastructure supporting the coordination for bio-banking with 20 country members and one international organization. Although the benefits of Biobanks to the research community are well established, the direct benefit to citizens is limited to the generic benefit of promoting future research. Furthermore, the advent of GDPR legislation raised a series of challenges for scientific research especially related to Biobanking associates activities, and longitudinal research studies. Electronic Health record (EHR) registries have long existed at health care providers. In some countries, even at the national level, these record the state of the health of citizens through time for the purposes of health-care, and data portability between different providers. The potential of EHR’s in research is great, and has been demonstrated in many projects that have transformed EHR data into retrospective medical history information on participating subjects directly from their physician’s collected records, many key challenges however remain. In this paper we present a citizen-centric framework called eHealthBioR that would enable Biobanks to link to Electronic Health Record systems, thus enabling not just retrospective, but also life-long prospective longitudinal studies of participating citizens. It will also ensure strict adherence to legal and ethical requirements, enabling greater control that encourages participation. Citizens would benefit from the real and direct control of their data and samples, utilizing technology, to empower them to make informed decisions about providing consent and practicing their rights related to the use of their data, as well as by having access to knowledge and data generated from samples they provided to Biobanks. This is expected to motivate patient engagement in future research, and even lead to participatory design methodologies with citizen/patient centric designed studies. The development of platforms based on the eHealthBioR framework would need to overcome significant challenges. However it would shift the burden of addressing these to experts in the field while providing solutions enabling in the long term the lower monetary and time cost of longitudinal studies coupled with the option of life-long monitoring through EHRs.